SCREENING OF ANTIBACTERIAL ACTIVITY OF NEOLAMARCKIA MACROPHYLLA LEAF CRUDE EXTRACT - Fazia, Mohamad Sinang; Izzarul Atirah, binti Boestamam; Ho Wei, Seng (2021)
Neolamarckia macrophylla (Roxb.) Bosser belongs to genus Neolamarckia of the family Rubiaceae which commonly known as the red kelampayan by the locals. It is an important timber tree that is used for reforestation, the woods used as raw materials of paper and plywood, while its bark used to relive fever in traditional medicine (Shi et al. 2020; Qalbi et al., 2019). The aim of this study was to determine the antimicrobial potential of N. macrophylla leaf crude extract. The crude extract was obtained using maceration technique using ethanol and distilled water as solvent for the extraction process. The antibacterial activities were screened against Escherichia coli, Pseudomonas aeruginosa, Salmonella typhimurium, Listeria monocytogenes, Staphylococcus aureus and Bacillus cereus with different concentration of the crude extract (12.5 mg/mL, 25 mg/mL, 50 mg/mL and 100 mg/mL) by using disc diffusion method. The test bacteria demonstrated inhibition zone between 7 to 10 mm with the linear increase of inhibition zone with concentration of extract. This findings provide preliminary results on the antibacterial potential of N. Macrophylla to be used in various application. Further purification of compounds might be necessary to explore more on its optimum potential.